Resource allocation for multiple-user multiple-antenna cellular systems - Trujillo Castañeda, Eduardo Daniel (2015)
The thesis addresses the sum rate or spectral e ciency maximization problem in cellular systems with two main components, multiple antennas and multiple users. In order to solve such a problem, several resource allocation techniques are studied and developed for di erent cellular scenarios. The antennas at the transmitters are arranged in several con gurations, i.e., co-located or distributed and for such arrangements di erent levels of coordination and cooperation between transmitters are investigated. Accounting for more receiver antennas than transmitter antennas implies that system optimization must select the best transmitter-receiver match (combinatorial problem) which can be solved with di erent degrees of cooperation between transmitters. The system models studied can be classi ed either as interference limited or as power limited systems. In interference limited systems the resource allocation is carried out independently by each transmitter which yield power leakage to unintended receivers. For this kind of systems, the access network using distributed antenna architectures is examined. The properties of distributed antenna in cellular systems as well as the gains they provide in terms of frequency reuse and throughput are assessed. Accounting for multiple user scenarios, several techniques and algorithms for transmitter-receiver assignment, power allocation, and rate allocation are developed in order to maximize the spectral e ciency. In power limited systems the transmitters jointly allocate resources among transmit and receive antennas. The transmitters are equipped with multiple antennas and signal processing is implemented in order to suppress inter-user interference. Single-cell and multi-cell systems are studied and the problem of sum rate maximization is tackled by decoupling the user selection and the resource allocation (power and precoding) processes. The user selection is a function of the type of precoding technique that is implemented and the level of information that can be processed at the transmitter. The developed user selection algorithms exploit information provided by novel channel metrics which establish the spatial compatibility between users. Each metric provides a di erent trade-o between the accuracy to identify compatible users, and the complexity required to compute it. Numerical simulations are used to assess the performance of the proposed user selection techniques (metrics and algorithms) whose performance are compared to state-of-the-art techniques.